Multi-channel seismic field data in Icy Bay and Taan Fjord, Alaska, acquired by the R/V Alaskan Gyre in 2016 (AG1608) (IEDA: Marine-Geo Digital Library, 2019)
Funded by the USGS Earthquake Hazards Program USGS-G16AP00150 and NSF (grant NSF-GLD-1638434), this 2016 R/V Alaskan Gyre survey (also known as USGS field activity 2016-654-FA) was a joint effort between the U.S. Geological Survey, the University of Texas Institute for Geophysics, and Texas A and M University. The survey collected 24-channel seismic data and multibeam data in Icy Bay and Taan Fjord, Alaska. The primary goal was to map and characterize offshore fault structures in Icy Bay associated with the Yakutat/North America deformation front. Secondary scientific objectives included characterizing the 2015 Taan landslide failure and modeling the resultant tsunami, mapping Icy Bay glacial deposits, examining tectonic controls on Taan Fjord, researching the geomorphology and slope processes in Taan Fjord, and identifying paleohazards (MTDs, paleoseismic events, etc.) within the region.